How does disease location affect acute phase reactants in ulcerative colitis? - Ipek, Serkan; Cekic, Cem; Alper, Emrah; Yalcin, Hulya; Toprak, Burak; Aslan, Fatih; Arabul, Mahmut; Unsal, Belkıs (International Journal of Research in Medical Sciences, 2017)
Background: We aimed to evaluate erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), white blood cell (WBC), platelet (PLT) counts and albumin levels according to disease location in ulcerative colitis. Methods: The ESR, CRP, WBC, PLT counts and albumin levels of 206 ulcerative colitis patients with endoscopic activity were retrospectively evaluated. Endoscopic activity had been assessed using Rachmilewitz endoscopic activity index. Patients were grouped according to the extent of disease by Montreal classification, and they were evaluated regarding the location and severity of disease according to the laboratory test results. Results: Among 206 patients, 88 (42.7%) had extensive colitis, 89 (43.2%) of them had left sided colitis and 29 (14%) patients had proctitis. According to the endoscopic activity index, 32.04% of the patients had mild activity, 39.32% moderate activity and 28.64% had severe activity. As the disease extent progressed from the distal to the proximal intestine, CRP, ESR, WBC and PLT counts showed a significant increase while albumin levels showed a significant decrease. In our study, the test that yielded the best results in the assessment of disease activity was CRP, which was found to be high in 80% of patients with extensive colitis, followed by ESR, PLT and WBC counts. As the involved intestine shortened, the rate of patients with abnormal laboratory tests significantly decreased Conclusion: CRP, ESR, WBC, PLT counts and albumin levels are of limited value in determining disease activity in ulcerative colitis patients, especially in those with proctitis